A Jurisprudential Critique of Khamr Prohibition in Abid Al-Jabiri’s Nuzuli Tafsir - Farabi, Fahmi Akhyar Al; Riyadi, Abdul Kadir; Iwanebel, Fejrian Yazdajird; Rafiuddin, Achmad; Amin, Faruq Aziz Al (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
Khamr, as an intoxicating substance, is explicitly prohibited in Islamic law due to its harmful effects on both individual and societal well-being. In Indonesia, the increasing number of khamr abuse cases has led to various social and health-related problems. Abid al-Jabiri, a contemporary Muslim intellectual, reexamines the prohibition of khamr through his nuzuli tafsir, offering a contextual and chronological understanding of the relevant Qur’anic verses. This study analyzes al-Jabiri’s nuzuli interpretation by applying a chronological approach to the verses on khamr prohibition (Q.S. al-Baqarah 2:219, al-Nisa’ 4:43, and al-Ma’idah 5:90–91), linking their stages of revelation with the sirah nabawiyyah. Using a library-based, descriptive-analytical method and the ijmali approach, the research traces the sequential development of the prohibition to uncover al-Jabiri’s juristic framework that integrates historical context with normative guidance. Through the lens of pragmatic truth theory, the study highlights the novelty of al-Jabiri’s nuzuli method, which contrasts with traditional, static interpretations by situating the verses within an evolving socio-political context. This reinterpretation offers a rational, adaptable, and socially responsive model for applying Islamic legal principles to contemporary issues, particularly concerning the regulation and understanding of intoxicants in modern Muslim societies.